Musical Instrumental Self-Concept, Social Support, and Grounded Optimism in Secondary School Students: Psycho-Pedagogical Implications for Music Education - Begoña Zarza-Alzugaray; Oscar Casanova; Francisco Javier Zarza-Alzugaray (Education Sciences, 2024)
Research in music education has shown that musical and academic self-concept, the social component, task achievement, and academic performance are highly interrelated constructs in musical learning in general and instrumental learning in particular in secondary school students. However, no studies in Spain have analyzed the relationship between musical self-concept and the variables of social support and optimism in compulsory secondary education. Therefore, our study aimed to explore the relationships between instrumental musical self-concept, social support, and grounded optimism. We hypothesize that there is a significant relationship between the variables of musical self-concept, social support, and grounded optimism The variables were measured using the Instrumental Musical Self-Concept Scale (IMSCS), an adaptation of the Perceived Social Support Scale in Spanish Conservatory Music Students to the Secondary School Level, and the Grounded Optimism Scale (BEEGC-RA/BEECESA-RA24). The study sample consisted of 980 students enrolled in compulsory secondary education in public and semi-private schools in the autonomous communities of Aragon and Navarra. An analysis of correlations and regressions allowed us to explore and quantify the relationship among the variables under study, confirming the existence of a significant relationship among the variables “instrumental musical self-concept”, “social support” and “grounded optimism”. The present study thus provides more in-depth knowledge of the variables involved in the teaching–learning process of music as a school subject and instrumental music in particular, as well as a greater knowledge of the individual’s performance and motivation in the subject, with various future implications to be taken into account.